Therapeutic prospect on umbilical cord mesenchymal stem cells in animal model with primary ovarian insufficiency: a meta-analysis - Wang, Xinrun; Li, Tianye; Bai, Xuechai; Zhu, Yun; Zhang, Meiliang; Wang, Liang (Frontiers in Medicine, 2023)
Background Primary ovarian insufficiency (POI) leads to not only infertile but several adverse health events to women. Traditional treatment methods have their own set of limitations and drawbacks that vary in degree. Application of human umbilical cord mesenchymal stem cell (hUCMSC) is a promising strategy for POI. However, there is a lack of literatures on application of hUCMSC in human. Animal experimental model, however, can reflect the potential effectiveness of this employment. This study aimed to evaluate the curative effect of hUCMSC on animals with POI on a larger scale. Methods To gather data, Pubmed, Embase, and Cochrane Library were searched for studies published up to April 2022. Various indices, including the animals' estrous cycle, serum sex hormone levels, and follicle number in the ovary, were compared between the experimental group and those with Premature Ovarian Insufficiency (POI). Results The administration of human umbilical cord-derived mesenchymal stem cells (hUCMSC) has been shown to significantly improve the estrous cycle (RR: 3.32, 95% CI: [1.80, 6.12], I2 = 0%, P = 0.0001), but robustly decrease its length (SMD: −1.97, 95% CI: [−2.58, −1.36], I2 = 0%, P < 0.00001). It can also strikingly increase levels of serum estradiol (SMD: 5.34, 95% CI: [3.11, 7.57], I2 = 93%, P < 0.00001) and anti-müllerian hormone (SMD: 1.92, 95% CI: [0.60, 3.25], I2 = 68%, P = 0.004). Besides, it lowers levels of serum follicle-stimulating hormone (SMD: −3.02, 95% CI: [−4.88, −1.16], I2 = 93%, P = 0.001) and luteinising hormone (SMD: −2.22, 95% CI: [−3.67, −0.76], I2 = 78%, P = 0.003), and thus collectively promotes folliculogenesis (SMD: 4.90, 95% CI: [3.92, 5.88], I2 = 0%, P < 0.00001). Conclusions Based on the presented findings, it is concluded that the administration of hUCMSC in animal models with POI can result in significant improvements in several key indicators, including estrous cycle recovery, hormone level modulation, and promotion of folliculogenesis. These positive outcomes suggest that hUCMSC may have potential as a treatment for POI in humans. However, further research is needed to establish the safety and efficacy of hUCMSC in humans before their clinical application. Systematic review registration https://inplasy.com/inplasy-2023-5-0075/, identifier: INPLASY202350075.